Evaluation of the Sustainability of Community-Based Drinking Water Supply Systems in Tasikmalaya Regency - Januar, Yeko Anugrah; Namara, Idi; Radisya Pratiwi, A Andini (Devotion : Journal of Research and Community Service, 2026)
The Tasikmalaya Regency Government developed a Community-Based Water Supply System (SPAM) to accelerate the achievement of the sixth Sustainable Development Goal (SDG). However, the infrastructure faces challenges in terms of sustainability, particularly in relation to operational failures, maintenance, and a lack of community ownership. Referring to Norms, Standards, Procedures, and Criteria (NSPK), this study aims to analyze the sustainability of SPAM management comprehensively through a multidimensional approach that covers technical, institutional, financial, social, and environmental aspects to formulate appropriate intervention priorities. The research method combines an analysis of existing conditions and stakeholder perceptions in five SPAM location units. Secondary data refers to NSPK provisions, while primary data was obtained through field observations and structured interviews with 90 community respondents and 27 relevant stakeholders. Data analysis techniques used the Relative Importance Index (RII) and Confidence Interval (CI) for key factors, the Index Formula for sustainability levels, and the Development Priority Index (IPP) to compile development factor priorities. The results of the study show that the status of SPAM management is in the sustainable category with an average index of 72.89%. The most crucial factor identified is the existence of community fees. The recommended development priorities include strengthening regulations as an operational foundation, balancing the financial aspects between the affordability of fees and maintenance costs, and optimizing the technical performance of pumps. These findings emphasize the need for an integrative strategy to ensure reliable and long-term clean water services for the community.